What is legislative productivity? Concepts and factors that explain it - Huertas-Hernández, Sergio (2025)
The purpose of this article is to systematize and critically analyze academic literature on the dynamics of entry and approval of bills in legislative bodies. So far, research has identified several variables that influence legislative productivity, including institutional, political-electoral, attitudinal factors and those intrinsic to the characteristics of the legislation itself. In this sense, we propose a theoretical review that seeks to answer the question: what are the factors that explain legislative productivity? To this end, legislative productivity is defined as the relationship between the number of bills presented and those that manage to be approved within the legislative process. From this analysis, it is argued that literature has privileged the study of institutional and political-electoral factors, relegating the exploration of endogenous variables to the law, which represents a gap in the research agenda. Consequently, this paper highlights the need to broaden the theoretical and methodological approach in legislative studies through greater consideration of endogenous variables, which could offer new perspectives on the determinants of legislative production.